Acceptability of integration of cervical cancer screening into routine HIV care, associated factors and perceptions among HIV-infected women: a mixed methods study at Mbarara Regional Referral Hospital, Uganda - Mackline Ninsiima; Agnes Nyabigambo; Joseph Kagaayi (BMC, 2023)
Abstract Background Integrating cervical cancer screening into routine Human Immunodeficiency Virus (HIV) care has been endorsed as an effective strategy for increasing uptake of cervical cancer screening, facilitating early detection and treatment of pre-cancerous lesions among HIV-infected women. In Uganda, this strategy has not been implemented yet in most HIV clinics. Assessing acceptability of this intervention among HIV-infected women is of great relevance to inform implementation. We assessed acceptability of integration of cervical cancer screening into routine HIV care, associated factors and perceptions among HIV-infected women enrolled in the HIV clinic at Mbarara Regional Referral Hospital. Methodology A mixed methods study utilizing explanatory sequential approach was conducted among 327 eligible HIV-infected women. Acceptability of integration of cervical cancer screening into routine HIV care was measured based on Theoretical Framework of Acceptability. Quantitative data was collected using a pre-tested questionnaire. We conducted focus group discussions to explore perceptions regarding the intervention among purposively selected HIV-infected women. Modified Poisson regression with robust variance analysis was utilized to determine factors associated with acceptability of the intervention. Statistical significance was determined at p-value <0.05. Thematic analysis utilizing inductive coding was applied to analyse qualitative data. Results The majority of HIV-infected women (64.5%) accepted integration of cervical cancer screening into routine HIV care. Religion, perceived risk of developing cervical cancer and ever screened for cervical cancer were statistically significantly associated with acceptability of integration of cervical cancer screening into routine HIV care. Perceived benefits of the proposed intervention were: convenience to seek for cervical cancer screening, motivation to undergo cervical cancer screening, improved archiving of cervical cancer screening results, confidentiality of HIV patient information, and preference to interact with HIV clinic health workers. Shame to expose their privacy to HIV clinic health workers and increased waiting time were the only perceived challenges of the integrated strategy. Conclusion Study findings highlight the need to take advantage of this acceptability to prioritize implementation of integration of cervical cancer screening into routine HIV care. HIV-infected women should be reassured of confidentiality and reduced waiting time to increase uptake of integrated cervical cancer screening and HIV services among HIV-infected women along the continuum of HIV care and treatment services.